Studies on ascaridid, oxyurid and enoplid nematodes (Nematoda) from fishes of the Okavango River, Botswana - Moravec, Frantisek; Van As, Liesl L (Folia parasitologica, 2015)
Based on light and scanning electron microscopical studies, eight species (five adult and three larval) of nematodes belonging to the Ascaridida, Oxyurida and Enoplida were collected from fishes of the Okavango River, Botswana, namely Falcaustra similis Moravec et Van As, 2004, Atractidae gen. sp. (only female) (both Cosmocercoidea), Cucullanus sp. (only female) (Seuratoidea), Cithariniella longicaudata sp. n., Synodontisia annulata sp. n. (both Oxyuroidea), Contracaecum sp. third-stage larvae, third-stage larvae of Galeiceps sp. (both Ascaridoidea) and Eustrongylides sp. fourth-stage larvae (Dioctophymatoidea). The new species Citharinella longicaudata (type host Schilbe intermedius Rüppel) is mainly characterised by the shape and size of cephalic papillae and the spicule 108 µm long, and Synodontisia annulata (type host S. intermedius) by the shape of cephalic papillae, body length of gravid females (4.88-5.33 mm) and a short spicule (66 µm long). The female specimen of Cucullanus sp. from Tilapia sparmanni Smith markedly differs from congeners parasitising inland fishes in Africa by the elongate pseudobuccal capsule and by the excretory pore far posterior to the oesophago-intestinal junction; apparently, it belongs to an undescribed species. Galeiceps larvae parasitising fishes are described for the first time. Cithariniella gonzalezi Van Waerebeke, Chabaud, Bain et Georges, 1988 is considered a junior synonym of C. khalili Petter, Vassiliadès et Troncy, 1972, and the previous records of Cithariniella citharini Khalil, 1964 from Synodontis spp. in Egypt concern, in fact, Cithariniella khalili Petter, Vassiliadès et Troncy, 1972. The specimens of Cithariniella reported by Koubková et al. (2010) from Paradistichodus dimidiatus (Pellegrin) in Senegal and misidentified as C. gonzalesi Van Waerebeke, Chabaud, Bain et Georges, 1988 are considered to represent a new species, C. koubkovae sp. n.; this is established by reference to the description and drawings provided by Koubková et al. (2010).
Keywords: helminth parasites; Africa; freshwater fish; Cithariniella; new species; Synodontisia; taxonomy; Galeiceps; Cucullanus